The Influence of Financial Performance Dimensions on Local Government Capital Expenditure Allocation - Rusdiah Hasanuddin; Elpisah Elpisah; Muslim Muslim (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
financial independence, effectiveness of GDP and the degree of contribution of BUMD to the allocation of capital expenditures of Gowa Regency. This research uses explanative research, which aims to test and obtain empirical evidence of the direct effect of financial performance on the allocation of regional government capital expenditures of Gowa Regency in 2002 until 2016. The data source used is secondary data using multiple linear regression method that is the method of analysis for more than one independent variable. Based on the test results found that the degree of decentralization and financial dependence have a negative and insignificant effect on the allocation of capital expenditure, financial independence has a positive and not significant effect on the allocation of capital expenditure while the effectiveness of GDP and the contribution of BUMD have positive and significant influence on the allocation of capital expenditure. Among the five independent variables, the most dominant effectiveness of GDP (X4) has an influence in the allocation of capital expenditure of the Gowa Regency Government compared to other variables.